2021
DOI: 10.3389/fgene.2021.673697
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Signatures of Selection Analyses Identify Loci Under Positive Selection in the Murrah Buffalo of India

Abstract: India is home to a large and diverse buffalo population. The Murrah breed of North India is known for its milk production, and it has been used in breeding programs in several countries. Selection signature analysis yield valuable information about how the natural and artificial selective pressures have shaped the genomic landscape of modern-day livestock species. Genotype information was generated on six buffalo breeds of India, namely, Murrah, Bhadawari, Mehsana, Pandharpuri, Surti, and Toda using ddRAD sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Some studies suggest that commercial pig breeds have larger proportions of IIb glycolytic fibers and rapid growth rates, which are thought to play important roles in determining meat quality. MYLK3 is involved in muscle cell development and the Ca 2+ signaling pathway in striated muscle contraction ( 24 ). MYH8 is a marker of muscle regeneration ( 25 ), and studies have shown that MYH8 expression dominates early skeletal muscle development ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that commercial pig breeds have larger proportions of IIb glycolytic fibers and rapid growth rates, which are thought to play important roles in determining meat quality. MYLK3 is involved in muscle cell development and the Ca 2+ signaling pathway in striated muscle contraction ( 24 ). MYH8 is a marker of muscle regeneration ( 25 ), and studies have shown that MYH8 expression dominates early skeletal muscle development ( 26 ).…”
Section: Discussionmentioning
confidence: 99%